Suckling and allosuckling behavior of dairy calves in indoor dam-rearing systems - Claire S. Wegner; Cady W. Chan; Lars Rönnegård; Lars Rönnegård; Sigrid Agenäs; Lena Lidfors; Hanna K. Eriksson (Frontiers in Veterinary Science)
An important element in dairy cow-calf contact (CCC) systems is to ensure sufficient milk intake by calves. However, little is known about possible changes in suckling behavior during suckling periods for calves up to 15 weeks old, and the prevalence of allosuckling is poorly understood in the context of these systems. This research had two aims: first, to explore possible changes in suckling behavior as calves aged when housed in an indoor CCC system, and second, to identify calf-level factors associated with allosuckling. Both aims were independently investigated in two separate studies (cow- and calf-driven contact, respectively) and involved both Swedish Red and Swedish Holstein dams and calves. In the cow-driven study, dam-calf pairs (n = 19 male and female calves) had shared access to a separate contact area containing stalls, which dams could leave at any time. In the calf-driven study, calves (n = 24 female calves) could access their dams (n = 23) in all parts of the pen, except the milking area. Behavior sampling from video was used to record suckling behaviors during a 24-h period at average calf ages of 3, 6, 9, 12 (both studies) and 15 (cow-driven only) weeks. In the cow-driven study, calves behaved consistently across all weeks in terms of suckling bout length and frequency. Calves in the calf-driven study took significantly fewer, but longer, suckling bouts as they aged. The overall frequency of allosuckling observed in the cow-driven study (36%) was higher than that in the calf-driven study (14%). However, the odds of allosuckling increased significantly with increasing calf age in both studies. Calves in the cow-driven study were observed to allosuckle even in the presence of their own dam, and increasingly so as they aged. For both studies, instances of allosuckling were over 140 times more likely when other calves were already engaged in suckling on a cow. We conclude that allosuckling is likely to occur in indoor dam-rearing systems when the animals are housed in automatic milking systems, although the frequency will depend on the age of the calves and the presence of other suckling calves.